Dailami warriors mediate the transmission of Sassanid military traditions to the Islamic world - mahmood seyyed; gholamreza shahrian (پژوهش‌های تاریخی ایران و اسلام, 2021)
After the collapse of the Sassanid Empire, its legacy in the field of governance, bureaucracy and other areas was transferred to the Islamic world and while adapting to the worldview and Islamic laws, it continued to live in a new guise.In the meantime, one of the legacies and traditions of Sassanid statehood that has been largely neglected is the military traditions, which most historians believe that with the conquest of Iran by Muslim Arabs and the collapse of the class system of the Sassanid, the military class will be out of existence forever and does not remain sign of them in the Islamic period.However, the elimination of the strong class of Sassanid armies does not mean the elimination of the heirs of this class and by studying the political-military changes of Iranian society in the process of transition from Sassanid to the Islamic era, one can well see the heirs of Sassanid military traditions in the presence of Dailami warriors who represented these traditions in all parts of the Islamic world until several centuries after Islam.